Albicetus oxymycterus, a New Generic Name and Redescription of a Basal Physeteroid (Mammalia, Cetacea) from the Miocene of California, and the Evolution of Body Size in Sperm Whales - Boersma, Alexandra T.; Pyenson, Nicholas D. (PLOS ONE, 2015)
Living sperm whales are represented by only three species (Physeter macrocephalus, Kogia breviceps and Kogia sima), but their fossil record provides evidence of an ecologically diverse array of different forms, including morphologies and body sizes without analog among living physeteroids. Here we provide a redescription of Ontocetus oxymycterus, a large but incomplete fossil sperm whale specimen from the middle Miocene Monterey Formation of California, described by Remington Kellogg in 1925. The type specimen consists of a partial rostrum, both mandibles, an isolated upper rostrum fragment, and incomplete tooth fragments. Although incomplete, these remains exhibit characteristics that, when combined, set it apart morphologically from all other known physeteroids (e.g., a closed mesorostral groove, and the retention of enameled tooth crowns). Kellogg originally placed this species in the genus Ontocetus, a enigmatic tooth taxon reported from the 19th century, based on similarities between the type specimen Ontocetus emmonsi and the conspicuously large lower dentition of Ontocetus oxymycterus. However, the type of the genus Ontocetus is now known to represent a walrus tusk (belonging to fossil Odobenidae) instead of a cetacean tooth. Thus, we assign this species to the new genus Albicetus, creating the new combination of Albicetus oxymycterus, gen. nov. We provide new morphological observations of the type specimen, including a 3D model. We also calculate a total length of approximately 6 m in life, using cranial proxies of body size for physeteroids. Lastly, a phylogenetic analysis of Albicetus oxymycterus with other fossil and living Physeteroidea resolves its position as a stem physeteroid, implying that large body size and robust dentition in physeteroids evolved multiple times and in distantly related lineages.